2012
DOI: 10.1111/jre.12007
|View full text |Cite
|
Sign up to set email alerts
|

Gingival advanced glycation end‐products in diabetes mellitus‐associated chronic periodontitis: an immunohistochemical study

Abstract: Gingival AGEs are increased in both type 1 and type 2 DM-associated periodontitis; however, the clinical parameter that determines their accumulation, and therefore their degree of influence on the development of DM-associated periodontitis, may be the duration of DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 52 publications
2
54
1
2
Order By: Relevance
“…Similarly, a synergistic effect on IL‐6 and IL‐8 has been reported in a condition presented with both AGEs and LPS in endothelial cells . Clinical and animal studies have demonstrated that diabetic subjects with periodontitis have significantly more AGEs in gingiva than do healthy controls . This implies that the level of AGEs is high in diabetic patients with periodontitis, even in the absence of exogenous/residual AGEs.…”
Section: Discussionmentioning
confidence: 78%
“…Similarly, a synergistic effect on IL‐6 and IL‐8 has been reported in a condition presented with both AGEs and LPS in endothelial cells . Clinical and animal studies have demonstrated that diabetic subjects with periodontitis have significantly more AGEs in gingiva than do healthy controls . This implies that the level of AGEs is high in diabetic patients with periodontitis, even in the absence of exogenous/residual AGEs.…”
Section: Discussionmentioning
confidence: 78%
“…In contrast, similar studies in endothelial cells demonstrated that E. coli LPS and AGE had a synergistic effect on the expression of IL‐6 and IL‐8 29 . Despite evidence for AGE accumulation in gingival tissues of patients with periodontitis, 25 to date, the effect of LPS from known periodontal pathogens, such as Porphyromonas gingivalis , on AGE‐induced expression of cytokines and chemokines by oral epithelial cells and monocytes is unknown.…”
mentioning
confidence: 96%
“…Despite a number of investigations into AGE and their role in the pathogenesis of T2DM‐associated periodontitis, 3 , 4 there is a paucity of data on T1DM. Indeed, to the best of the authors’ knowledge, there is only one clinical study that demonstrates that AGE accumulation in the gingivae of patients with periodontitis was common to both T1DM and T2DM, although the key factors associated with AGE accumulation were not clear 25 . Stimulation of monocytes in vitro with AGE has been found to induce expression of IL‐6 26 and IL‐8 27 .…”
mentioning
confidence: 99%
“…Such results were confirmed in vivo where AGE deposition and RAGE expression were considerably elevated in the later stages in animals with diabetes even in animals without diabetes but with periodontitis 27 . In humans, AGEs have been shown to be increasingly expressed in the periodontium of diabetic patients 28 , and also significantly associated with deterioration of periodontitis, whereas no other serum biochemical marker or bacterial occurrence showed a clear relationship with that condition 29 . However, other studies in humans have shown no extreme differences in periodontal clinical parameters, according to different glycemic control 30 .…”
Section: Discussionmentioning
confidence: 99%